Syntax: a generative introduction - Carnie,A. Andrew Carnie (UK: Wiley Blackwell, 2021)
Now in its fourth edition, Andrew Carnie's Syntax: A Generative Introduction remains the leading introduction to the rules, principles, and processes that determine the structure of sentences in language. Comprehensive yet accessible, the text provides a well-balanced, student-friendly introduction to syntactic theory. Topics include phrase structure, the lexicon, binding theory, case theory, movement, covert movement, locality conditions, ditransitives, verbal inflection and auxiliaries, ellipsis, control theory, non-configurational languages, and more. Students are provided with numerous exercises and pedagogical features designed to strengthen comprehension, review learning objectives, test knowledge, and highlight major issues in the field. The fourth edition features revised material throughout, including a new section on Chomsky's Merge and additional problem sets in every chapter, while new examples throughout the text broaden the appeal and relatability of the text to a more diverse set of students. The optional The Syntax Workbook: A Companion to Carnie's Syntax has also been thoroughly revised and expanded to offer students the opportunity to practice the skills and concepts introduced in the primary text. This classic textbook
includes bibliography references and index